2018
DOI: 10.7759/cureus.2346
|View full text |Cite
|
Sign up to set email alerts
|

Daily Tracking of Glioblastoma Resection Cavity, Cerebral Edema, and Tumor Volume with MRI-Guided Radiation Therapy

Abstract: Radiation therapy (RT) plays a critical role in the treatment of glioblastoma. Studies of brain imaging during RT for glioblastoma have demonstrated changes in the brain during RT. However, frequent or daily utilization of standalone magnetic resonance imaging (MRI) scans during RT have limited feasibility. The recent release of the tri-cobalt-60 MRI-guided RT (MR-IGRT) device (ViewRay MRIdian, Cleveland, OH) allows for daily brain MRI for the RT setup. Daily MRI of three postoperative patients undergoing RT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 10 publications
0
29
0
1
Order By: Relevance
“…The lack of significant changes in HD and D0.03 cc for the set of all OARs together was likely due to the small sample size. The change in OARs may be in part due to changes observed in the tumor, resection cavity volume, and associated intracranial edema during adjuvant CRT . Compared to the static contours, the propagated contours had a significantly higher DSC, lower HD, and lower absolute ΔD0.03 cc, demonstrating that semi‐automatic contour propagation is able to track changes in the OARs.…”
Section: Discussionmentioning
confidence: 96%
“…The lack of significant changes in HD and D0.03 cc for the set of all OARs together was likely due to the small sample size. The change in OARs may be in part due to changes observed in the tumor, resection cavity volume, and associated intracranial edema during adjuvant CRT . Compared to the static contours, the propagated contours had a significantly higher DSC, lower HD, and lower absolute ΔD0.03 cc, demonstrating that semi‐automatic contour propagation is able to track changes in the OARs.…”
Section: Discussionmentioning
confidence: 96%
“…Although the pipeline was built using different patients for the registration task as a proof of concept, such tool could have numerous applications in clinical practice, especially when applied in different images acquired from the same patient. Regarding the radiotherapy treatment planning, several studies have shown that significant changes of the targeted volumes in the brain occurred during radiotherapy raising the question of replanning treatment to reduce the amount of healthy brain irradiated in case of tumor reduction, or to re-adapt the treatment for brain tumors that grow during radiation (Champ et al, 2012;Yang et al, 2016;Mehta et al, 2018). Since MR-guided linear accelerator will offer the opportunity to acquire daily images during RT treatment, the proposed tool could help with automatic segmentation and image registration for replanning purposes, and it could also allow accurate evaluation of the dose delivered in targeted volumes and healthy tissues by taking into account the different volume changes.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike extra-cranial localizations, data on adaptive RT for brain tumors is sparse in spite of the fact that GBM is known as a rapidly growing tumor type, and CRT is applied postoperatively when relevant changes in post-surgical and tumor volume are supposed to occur (5,(9)(10)(11)(12)37). Both internationally applied guidelines (RTOG and EORTC) define target volume based on surgical cavity, edema and residual tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Toward that goal, many newly defined structures have to be delineated. Furthermore, if the volume and location of the primarily contoured structures change, particularly small structures (such as chiasma, subventricular zone (SVZ) and hippocampus), those should also be followed and the RT plan subsequently modified (5). Several studies have investigated spatial and dosimetric changes in critical structures during treatment for different cancer types (6)(7)(8), but much less research has been performed on RT of the brain, which has great anatomical constancy due to the closed skull volume and lack of organ movement.…”
mentioning
confidence: 99%